William Blake : modernity and disaster - Rajan, Tilottama; Faflak, Joel (University of Toronto Press, 2020)
"William Blake: Modernity and Disaster explores the work of the Romantic writer, artist, and visionary William Blake as a profoundly creative response to cultural, scientific, and political revolution. In the wake of such anxieties of discovery, including the revolution in the life sciences, Blake's imagination - often prophetic, apocalyptic, and deconstructive - offers an inside view of such tumultuous and catastrophic change. A hybrid of text and image, Blake's writings and illuminations offer a disturbing and productive exception to accepted aesthetic, social, and political norms. Accordingly, the essays in this volume, reflecting Blake's unorthodox perspective, challenge past and present critical approaches in order to explore his oeuvre from multiple perspectives: literary studies, critical theory, intellectual history, science, art history, philosophy, visual culture, and psychoanalysis. Covering the full range of Blake's output from the shorter prophecies to his final poems, the essays in William Blake: Modernity and Disaster predict the discontents of modernity by reading Blake as a prophetic figure alert to the ends of history. His legacy thus provides a lesson in thinking and living through the present in order to ask what it might mean to envision a different future, or any future at all."--